1966
DOI: 10.1111/j.1600-0447.1966.tb08801.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of Neuroleptic Drug Action, Particulary Considering Butyrophenones.

Abstract: In his attempts to estimate the comparative value and potency of a neuroleptic agent the clinician may frequently find his primary impressions corrected or modified through prolonged and extensive use of the drug in question,The "fate" of the butyrophenone derivative floropipamide (DipiperonB) in this hospital may serve as an illustration. As a result of a pilot study conducted in 1963 on 70 schizophrenic women we were inclined to classify this drug as a potent anti-psychotic agent, similar in action to the pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1973
1973
1976
1976

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Chemical and pharmacological classifications have been made, but they are of limited value from the clinical point of view. Various clinical classification models have been suggested, most of them of the bipolar type such as the one constructed by one of us (Kristjansen 1974), comprising the most widely used of the neuroleptics put on the market in Scandinavia (Fig 1). In a classification of this type the neuroleptic drugs are divided into those given in high Collard 1974) dosages and having pronounced sedative and anxiolytic effect and, via a middle group, those which are effective at a low dosage level and possess more specific antipsychotic properties.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Chemical and pharmacological classifications have been made, but they are of limited value from the clinical point of view. Various clinical classification models have been suggested, most of them of the bipolar type such as the one constructed by one of us (Kristjansen 1974), comprising the most widely used of the neuroleptics put on the market in Scandinavia (Fig 1). In a classification of this type the neuroleptic drugs are divided into those given in high Collard 1974) dosages and having pronounced sedative and anxiolytic effect and, via a middle group, those which are effective at a low dosage level and possess more specific antipsychotic properties.…”
mentioning
confidence: 99%
“…During the last ten years, several papers have presented suggestive evidence for the fact that some schizophrenics actually do better without continuous administration of antipsychotic drugs (Kristjansen 1966, Levine 1974). In our laboratory Schi0rring (1972) has shown that in animal experiments neuroleptics may disrupt social interaction, suggesting that drugs in some cases may be increasing autism rather than reducing it, and a clinical study from our hospital (Gerlach & Luhdorf 1975) found a certain antiautistic effect of levodopa on younger male schizophrenics.…”
mentioning
confidence: 99%